Yakámokeno (listen!): contributions of the Terena indigenous cosmovision to dance and education: (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This text presents part of a Post-doctoral research that focused on the indigenous cosmovision of the Terena ethnic group from Mato Grosso do Sul as a source of knowledge for scenic dance and education. Two aspects of the indigenous cosmovision were addressed - their relationship with ecology and with expanded states of consciousness - contributing to theoretical discussion and choreographic composition. Indigenous authors from different Brazilian ethnicities were used, such as Kaká Werá, Davi Kopenawa, and Rosa Maria Marchewicz, to repair the absence of their voices in academic research and the consequent devaluation of their knowledge in the Brazilian scene and education.
Keywords: indigenous cosmovision; ecology; expanded states of consciousness; danse; educaci; education